Innovation in Design and Construction of Posyandu Information System as a Web-Based Toddler Growth and Development Monitoring Solution in Sukabakti Village, Tarogong Kidul, Garut Regency - Alia Tri Utami; Sulthan Muhamad Rifki; Dewi Dennyta (Jurnal Pengabdian Masyarakat: Bisnis dan Iptek (JPMBISTEK), 2024)
To prevent stunting, the *Pos Pelayanan Terpadu* (Posyandu) is a community-managed healthcare program offering essential health services by monitoring children's growth and development. Universitas Muhammadiyah Bandung lecturers and students worked on a project to address the manual procedures still in place in Posyandu for data collection, reporting, and monitoring activities. The group's main goal was to create a web application that included important elements such as a dashboard, anthropometric data for toddlers, and growth and development tracking for toddlers. The main objective of this initiative was to enhance the effectiveness and security of toddler growth data collection, especially for Posyandu cadres. To maximize the application's use, Posyandu cadres were trained in information technology development and utilization. As the project's result, the Posyandu Sukabakti web application was successfully implemented. The software development process used the Rapid Application Development (RAD) methodology. In conclusion, the community service effort at Posyandu in Sukabakti Village has yielded significant benefits. The adopted solution has greatly simplified the management of toddler data at Posyandu Sukabakti, Tarogong Kidul, and Garut Regency for Posyandu cadres. This streamlined process has improved the efficiency and accuracy of data collection and reporting, ultimately contributing to the prevention of stunting in the community.